2017
DOI: 10.1186/s12917-017-1231-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of culturable fungi from the genitals and semen of healthy giant pandas (Ailuropoda melanoleuca)

Abstract: BackgroundIn order to better understand the possible role of fungi in giant panda reproduction and overall health, it is important to provide a baseline for the normal fungal composition in the reproductive system. Using morphology and internal transcribed spacer (ITS) sequence analysis, we systematically isolated and identified fungal species from the vagina, foreskin, and semen of 21 (11 males and 10 females) healthy giant pandas to understand the normal fungal flora of the genital tracts.ResultsA total of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Pandas that had been treated with antifungal drugs during the previous 6 months or with a recent history of disease were excluded from this study. The pandas lived in a semi-captive semi-enclosed breeding environment, were fed a diet of about 10% steamed cornbread and fruits and 90% bamboo shoots, and were allowed to drink water ad libitum (14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pandas that had been treated with antifungal drugs during the previous 6 months or with a recent history of disease were excluded from this study. The pandas lived in a semi-captive semi-enclosed breeding environment, were fed a diet of about 10% steamed cornbread and fruits and 90% bamboo shoots, and were allowed to drink water ad libitum (14).…”
Section: Methodsmentioning
confidence: 99%
“…No repeat sampling was performed on the same panda, and all 44 samples were processed with isolated Trichosporon spp. (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The giant panda ( Ailuropoda melanoleuca ) is one of the rarest endangered animals[1, 2]. Dermatomycosis has become the second major disease of giant pandas, which seriously affect the survival of giant pandas [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that Trichosporon spp. is the dominant genera of the body surface [4] and genitals of giant pandas [2]. These species may lead to trichosporidiosis in humans and animals.…”
Section: Introductionmentioning
confidence: 99%